Barriers and solutions to economic integration of Caspian Sea countries - Ulviyye Aydin (Asian Development Bank Institute (ADBI), 2020)
The aim of this paper is to analyze the barriers to economic integration of Caspian Sea countries - specifically the Russian Federation, Kazakhstan, Azerbaijan, Turkmenistan, Uzbekistan, Iran, and Georgia - and suggest solutions. A literature review is used as a methodology for conducting this research, synthesizing research findings to determine the current level of integration in the Caspian Basin, barriers to it, and to uncover solutions that can deepen it. It was concluded from this research that Caspian states have a long experience of economic integration. However, it was found that the obstacles that prevent economic integration among Caspian states can be summarized under three main headings. First of all, the geographic location of Caspian states is so critical that it is impossible to define clear borders in the region. Second, the different governance structures of Caspian states make it difficult to evaluate the co-benefits of economic integration. Third, the geopolitical interests of foreign actors are a serious handicap for the region's economic integration. On the other hand, ongoing geopolitical and economic processes are increasing Caspian states' need for each other. In this context, existing bilateral and trilateral agreements can be classified by the number of sides and subjects so that a multi-speed integration can be achieved among the region's countries and they can choose the level of integration according to their own interests.
Keywords: F02; F15; F50; 330; Caspian Sea; economic integration; energy cooperation; geopolitical interests